Życie prywatne. Malarstwo historycznej anegdoty w prasie ilustrowanej drugiej połowy XIX wieku na przykładzie dzieł sztuki o tematyce życia Zygmunta Augusta i jego romansu z Barbarą Radziwiłłówną = Private life. The painting of historical anecdote in the illustrated press of the second half of the 19th century on examples representing the live of Sigismund II August and his love affair with Barbara Radziwiłł - Pijanowska, Kamila (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In the second half of the 19th century Polish illustrated magazines published - among oth?ers - reproductions of historical paintings. For the editors, the scenes from the Polish history were the most important. Artists created monumental works which fuzed the effect of complex historical processes into one picture, but also searched for anecdotes from the private life of past characters.
Keywords: czasopisma; malarstwo historyczne; reprodukcje dzieł sztuki; sztuka polska; prasa ilustrowana; magazines; historical painting; art reproduction; Polish art; illustrated press